Variability of Unofficial Names of the Sculpture Embankment Arch of Vilnius - Sidaravičienė, Veslava (Slavistica Vilnensis, 2024)
The article discusses variability of the unofficial names for Vladas Urbanavičius's sculpture Krantinės Arka (The Embankment Arch) in the language of Lithuanians, born in 1989–1998, according to the methods of their formation. Variants of names of the sculpture are compared to the equivalents used by the local Russians and Poles. This sculpture is commonly referred to as Vamzdis (The Pipe) in the unofficial Lithuanian language. In multi-word names where the nomenclature word is pipe, the unique part of the name highlights the external characteristics of the sculpture, its purpose, indicates the place where it stands, describes its meaning, or expresses a negative attitude, for example, Baisus vamzdis (A Terrible Pipe), Šūdų vamzdis (A Pipe of Shit), Išmatų vamzdis (A Pipe of Excrement). Sculpture Krantinės arka (The Embankment Arch) is called Rura (The Pipe) or Trąba [Tromba] (The Pipe) by Poles, and Труба (The Pipe) by Russians. These names reveal the similarities in the worldview of Vilnius Lithuanians, Russians and Poles: the basis of the same names ​​is the form of the object, with the difference being linguistic.
Keywords: variability; unofficial urbanonyms; urbanonyms; names of sculpture; spoken language